Duchenne muscular dystrophy: an historical treatment review - Lineu Cesar Werneck; Paulo José Lorenzoni; Renata Dal-Prá Ducci; Otto Hernández Fustes; Cláudia Suemi Kamoi Kay; Rosana Herminia Scola (Arquivos de Neuro-Psiquiatria)
ABSTRACT In this review, we discuss the therapies used in the treatment of patients with Duchenne muscular dystrophy since the first description of the disease. A short description is given of the various theories based on disease pathogenesis, which give the substrates for the many therapeutic interventions. A brief review of the methods of evaluation used in therapeutic trials is made. Of all the treatments, the only drugs that are still considered able to modify the course of the disease are the corticosteroids (prednisone/prednisolone/deflazacort). Other drugs (coenzyme Q10 and creatine) have had a little effect in a few functions without adverse reactions. Idebenone seems to improve the respiratory function in the long term. The trials with mRNA transcription, through nonsense mutations or exon 51 skipping, show some beneficial results in a few functional tests, but they are limited to a small set of DMD patients.